Beasts of Carnaval - Rodrigo, Rosália (Mira, 2025)
A Puerto Rico-inspired fantasy follows a woman recently freed from slavery as she searches for her missing brother at the Carnaval of Beasts and learns why nobody who enters Carnaval ever leaves.